Multi-Drug Resistant Escherichia coli, Biosecurity and Anti-Microbial Use in Live Bird Markets, Abeokuta, Nigeria - Oluwawemimo Adebowale; Motunrayo Makanjuola; Noah Bankole; Mary Olasoju; Aderonke Alamu; Eniola Kperegbeyi; Oladotun Oladejo; Olubunmi Fasanmi; Olanike Adeyemo; Folorunso O. Fasina (MDPI AG, 2022)
Live bird markets (LBM) remain a critical link from farm to fork in the poultry value chain, which oftentimes promotes indiscriminate antimicrobial use (AMU) and resistance (AMR). In this study, we assessed biosecurity practices, AMU, and associated these with multidrug resistant (MDR) E. coli in LBMs in Abeokuta, Ogun State. A cross-sectional survey among live bird sellers (LBS) in eight LBMs was conducted using a semi-structured questionnaire. Also, cloacal samples (n = 200) were randomly collected and pooled for bacteriological detection of MDR E. coli in live chickens of consenting LBS. Susceptibility to 14 antimicrobials belonging to 6 different classes was determined using the disk diffusion method. Biosecurity level and AMU were generally low. LBS less than 46 years were 6.8- fold more likely to fall within the poor biosecurity level (Crudes odds ratio = 6.8; 95% CI; 1.20-38.56; p = 0.03) than others. An informal or primary school education increased the odds of having a poor practice of AMU by 15.1 folds (Crudes odds ratio = 15.1; 95% CI; 2.73-84.18; p = 0.002) than those with secondary or tertiary. The prevalence of E. coli and MDR E. coli at the LBM level were 80% and 56.3%, respectively. Extremely high resistance rates were observed for ceftazidime (96.9%) and imipenem (90.6%). The odds of MDR E. coli increased eight-fold in poultry kept by LBS who use AMs as prophylaxis. This current data could be useful for the development of targeted behavioral risk communication and mitigation strategies for AMR to impede the potential horizontal transfer of AMR genes to humans through animal-sourced food.